Cover Picture: Wound Pathogens: Investigating Antimicrobial Activity of Commercial Essential Oil Combinations against Reference Strains (C&B 12/2018). Issue 12 (5th December 2018) - Orchard, Ané; Viljoen, Alvaro; van Vuuren, Sandy
Abstract : Cover Picture . Essential oil combinations were investigated against pathogens most frequently found in wounds. From this study, the importance of scientific validation is emphasised, especially considering that the recommended aroma‐therapeutic combinations did not always result in the predicted efficacy. Furthermore, only a slight variation in antimicrobial activity exists between different chemotypes of essential oils, yet synergy was more common in the chemotype that displayed the more notable antimicrobial activity. Essential oil combinations as a viable option in wound therapy are reported by Orchard et al . in their full paper at10.1002/cbdv.201800405 .